Film Animasi “Inside Out 2” sebagai Media Edukasi Mengenai Kecemasan Remaja - Adiwinata, Arcelia Emmanuella; Winduwati, Septia (Koneksi, 2025)
The development of technology and information presents various types of media as information channels to the public, one of which is through films. Film as an audio-visual medium involves the concept of signs and symbols to convey meaning, messages, and significance to the audience. The researcher is interested in studying a film entitled “Inside Out 2” which aims to determine the representation form of teenage anxiety. This research was conducted because of the increasing rate of anxiety in teenagers, especially in Indonesia, with minimal learning to control emotions. The theories and concepts used in this research include the theory of mass communication, film, semiotics, representation, mental health, and anxiety. The approach employed is a descriptive, qualitative method with semiotic techniques. The subject of this research is the film Inside Out 2, and the object is the representation of teenage anxiety in the movie. Researchers collected data through documentation, which will be analyzed using Ferdinand de Saussure's semiotics, as well as through interviews with experts. Researchers found signs regarding the representation of teenage anxiety in 12 scenes. Several representation forms include excessive anxiety, negative thought patterns, low self-esteem and insecurity, extreme actions, bad self-identity, aggressive behavior and selfish attitudes, poor emotional expression and regulation, as well as a closed attitude and harboring emotions. Perkembangan teknologi dan informasi menghadirkan berbagai macam media sebagai saluran informasi kepada khalayak, salah satunya melalui film. Film sebagai sebuah media audio visual melibatkan konsep tanda dan simbol untuk penyampaian arti, pesan, dan makna kepada penontonnya. Peneliti tertarik untuk mengkaji sebuah film berjudul “Inside Out 2” yang bertujuan untuk mengetahui bentuk representasi kecemasan remaja. Penelitian ini dilakukan karena meningkatnya angka kecemasan remaja, khususnya di Indonesia, namun minimnya pembelajaran pengendalian emosi kepada remaja. Teori dan konsep yang digunakan penelitian ini adalah teori komunikasi massa, film, semiotika, representasi, kesehatan mental, dan kecemasan. Pendekatan yang diaplikasikan adalah pendekatan kualitatif deskriptif dengan metode semiotika. Subjek penelitian ini adalah film Inside Out 2 dan objeknya adalah representasi kecemasan remaja dalam film. Peneliti melakukan pengumpulan data melalui dokumentasi yang akan dianalisis menggunakan semiotika Ferdinand de Saussure serta wawancara dengan pihak ahli. Peneliti menemukan adanya tanda – tanda mengenai representasi kecemasan remaja dalam 12 adegan yang memberikan penggambaran kecemasan remaja. Beberapa bentuk representasi meliputi kecemasan berlebihan, pola pikir negatif, harga diri rendah dan kurang percaya diri, tindakan ekstrem, jati diri buruk, perilaku agresif dan sikap egois, ekspresi dan regulasi emosi yang buruk, serta sikap tertutup dan memendam emosi.